The Oxford handbook of employment relations : comparative employment systems - Wilkinson, Adrian, 1963-; Wood, Geoffrey E., 1945-; Deeg, Richard, 1961- (Oxford handbooks in business and management., 2014)
This handbook is a comparative treatment of employment relations, providing frameworks and empirical evidence for understanding trends in different parts of the world.